2021
DOI: 10.3390/nu13103668
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain Associated with COVID-19 Lockdown in Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Background: Lockdown is an effective nonpharmaceutical intervention to reduce coronavirus disease 2019 (COVID-19) transmission, but it restricts daily activity. We aimed to investigate the impact of lockdown on pediatric body weight and body mass index (BMI). Methods: The systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement. Four online databases (EMBASE, Medline, the Cochrane Library and CINAHL) were searched. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
144
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(199 citation statements)
references
References 32 publications
10
144
3
2
Order By: Relevance
“…Similarly, in another study, a semi-lockdown increased BMI of 70.3% of volleyball players in Cameroon [ 22 ]. A recent systematic review and meta-analysis showed significant increases in body mass and BMI during the lockdown in school-age children and adolescents due to physical inactivity and sedentary behavior [ 20 , 37 ]. A study conducted in Spain during the COVID-19 confinement showed a reduction of weekly minutes of physical activity during the confinement by 51.6%, and an increase of daily hours of screen exposure, i.e., TV watching and game playing (+2.9 ± 2.1 h) in 860 male and female children aged between 3 and 16 years [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study, a semi-lockdown increased BMI of 70.3% of volleyball players in Cameroon [ 22 ]. A recent systematic review and meta-analysis showed significant increases in body mass and BMI during the lockdown in school-age children and adolescents due to physical inactivity and sedentary behavior [ 20 , 37 ]. A study conducted in Spain during the COVID-19 confinement showed a reduction of weekly minutes of physical activity during the confinement by 51.6%, and an increase of daily hours of screen exposure, i.e., TV watching and game playing (+2.9 ± 2.1 h) in 860 male and female children aged between 3 and 16 years [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the beginning of the worldwide COVID-19 pandemic and the associated restrictions on physical activity and temporary bans (mostly during lockdown phases) on organized sports in general and in schools, the already serious obesity pandemic underwent a worrisome acceleration [ 37 , 38 , 39 , 40 , 41 ] and health-related fitness scores showed dramatic decreases [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with other studies who investigated the lockdown influence on populations other than children with DS. Chang et al [ 17 ] and Mohr et al [ 18 ] reported that containments led to reduced physical activities and excess food consumption, weight gain, and behavioral disorders. The participants in this study manifested variable comorbidities, microcephaly, growth retardation, or obesity which were detected by anthropometric measures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, abnormal collagen structure, which is crucial for muscle integrity, was detected in these people and was linked to aberrant COL6A3 gene signaling [ 5 ]. Furthermore, the shape of the pelvic spinal area and hips in people with DS differs, which could disrupt their gait [ 17 ]. All these factors could have limited the progress despite having virtual physical therapy rehabilitation sessions.…”
Section: Discussionmentioning
confidence: 99%